2014
DOI: 10.1177/2050640614520865
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of cyclosporin rescue therapy in acute, steroid‐refractory severe ulcerative colitis

Abstract: Cyclosporin is effective in acute, severe UC during long-term follow up. Our data suggest that the longer cyclosporin is used, the more it is possible to avoid colectomy in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…While the duration of optimal therapy is yet to be established, in a retrospective study, Molnar et al . found that treatment for 1 year correlated with a 66% probability of avoiding colectomy at 4‐year follow‐up and beyond . Further prospective studies are needed to confirm this association.…”
Section: Salvage Therapiesmentioning
confidence: 93%
See 3 more Smart Citations
“…While the duration of optimal therapy is yet to be established, in a retrospective study, Molnar et al . found that treatment for 1 year correlated with a 66% probability of avoiding colectomy at 4‐year follow‐up and beyond . Further prospective studies are needed to confirm this association.…”
Section: Salvage Therapiesmentioning
confidence: 93%
“…There has been recent suggestion that more extended durations of therapy may enhance greater durability of remission and improve rates of colectomy‐free survival . While the duration of optimal therapy is yet to be established, in a retrospective study, Molnar et al .…”
Section: Salvage Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are several medications on the market for IBD, they generally only provide temporary relief, and 70% of IBD patients require surgical intervention (2). Because the current treatments are not satisfactory, new drug leads are being sought from a range of sources, including small molecules from plants and bioactive regions of larger proteins (3)(4)(5)(6).…”
mentioning
confidence: 99%